A simulation and analytic hierarchy process based decision support system for air cargo warehouse capacity design. (March 2022) - Sencer, Asli; Karaismailoglu, Adnan
Warehouse design is critical in the air cargo industry, where service standards are high and competition is fierce. The designers of air cargo warehouses consider various criteria like costs, system failure risks, customer perception, and marketing power to evaluate alternative designs. The issue of designing an air cargo warehouse is generally considered by design and consulting companies, which have broad experience in operational design are lacking in suggesting robust alternatives that build upon on a well-structured theoretical framework. The alternative warehouse designs are generated by considering different combinations of resource capacities such as the number of gates, workstations and storage areas. The evaluation of these alternative designs requires the use of analytical methodologies for multi-criteria decision-making. At this point, two methodologies from literature may be helpful: (i) simulation, which is a popular tool to evaluate operational performance and (ii) the analytical hierarchy process (AHP), which provides the ability to evaluate qualitative as well as quantitative criteria. In this study, a flexible and user-friendly decision support system (DSS) is developed based on combining simulation and AHP. The DSS is used to generate design alternatives, evaluate their quantitative performance via simulation, and subsequently rank the best scoring ones via AHP according to a set of quantitative as well as qualitative decision criteria. The graphical interfaces are designed with a keen eye on man-machine interaction to increase their functionality. The environment is tested and validated with real-time data in one of Europe's largest air cargo carriers.